Optical-thermal response of laser-irradiated tissue - Welch, Ashley J.; Gemert, Martin J.C (Springer, 2011)
The second edition of 'Optical-Thermal Response of Laser-Irradiated Tissue' maintains the standard of excellence established in the first edition, while adjusting the content to reflect changes in tissue optics and medical applications since 1995. The material concerning light propagation now contains new chapters devoted to electromagnetic theory for coherent light. The material concerning thermal laser-tissue interactions contains a new chapter on pulse ablation of tissue. The medical applications section now includes several new chapters on Optical Coherent Tomography, acoustic imaging, molecular imaging, forensic optics and nerve stimulation. A detailed overview is provided of the optical and thermal response of tissue to laser irradiation along with diagnostic and therapeutic examples including fiber optics. Sufficient theory is included in the book so that it is suitable for a one or two semester graduate or for senior elective courses. Material covered includes: 1. light propagation and diagnostic application; 2. the thermal response of tissue and therapeutic application; 3. denaturation; 4. ablation. The theory and applications provide researchers with sufficient detail that this volume will become the primary reference for laser-tissue interactions and medical applications.